2018
DOI: 10.1007/s00702-018-1931-z
|View full text |Cite
|
Sign up to set email alerts
|

Chronic oral methylphenidate treatment increases microglial activation in rats

Abstract: Methylphenidate (MP) is a widely prescribed psychostimulant used to treat attention deficit hyperactivity disorder. Previously, we established a drinking paradigm to deliver MP to rats at doses that result in pharmacokinetic profiles similar to treated patients. In the present study, adolescent male rats were assigned to one of three groups: control (water), low-dose MP (LD; 4/10 mg/kg), and high dose MP (HD; 30/60 mg/kg). Following 3 months of treatment, half of the rats in each group were euthanized, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…Early-life exposure to high doses of potentially toxic chemicals (GBR12909 [92], valproate [93], methylphenidate [94], manganese [95]) impacts microglia with very similar results in the short term. Specifically, increases in cell number, amoeboid/hypertrophic morphology, and expression of activation markers (CD68) have been found across brain regions, including frontal and other cortices, HIP, AMY, striatum, thalamus, substantia nigra, and globus pallidus [92][93][94][95][96].…”
Section: Postnatal Environmental Agents and Infectionmentioning
confidence: 99%
“…Early-life exposure to high doses of potentially toxic chemicals (GBR12909 [92], valproate [93], methylphenidate [94], manganese [95]) impacts microglia with very similar results in the short term. Specifically, increases in cell number, amoeboid/hypertrophic morphology, and expression of activation markers (CD68) have been found across brain regions, including frontal and other cortices, HIP, AMY, striatum, thalamus, substantia nigra, and globus pallidus [92][93][94][95][96].…”
Section: Postnatal Environmental Agents and Infectionmentioning
confidence: 99%
“…The notion of dysregulated dopaminergic neurotransmission was also established in the pathophysiology of various diseases such as schizophrenia and bipolar disorder [33]. Notably, the locomotor hyperactivity induced by MPH has been reported [11] which is associated by a robust increment in DA release in the PFC [34]. This upsurge is attributed not only to MPH ability to increase DA release but also to inhibition of dopamine transporter (DAT) [35] with subsequent decrease in DA uptake an effect mediated by PKC-α phosphorylation of N-terminal of DAT [9,36].…”
Section: Discussionmentioning
confidence: 99%
“…For example, there are no prominent therapies for the symptomatic relief of ASD. Methylphenidate, a drug commonly used for the treatment of ADHD, can cause hyperactivity, which is also a symptom of ADHD [ 104 ]. In the case of epilepsy, many types of anticonvulsants have been developed and are in clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it has been reported that methylphenidate hydrochloride (MP)-treated rats showed increased microglial activity in multiple regions of the brain (such as the insular cortex, hippocampus, and thalamus) [ 104 ]. MP is widely used in therapies for various psychiatric diseases, including ADHD and chronic sleep disorders.…”
Section: Asd (Autism Spectrum Disorder) and Adhd (Attention-deficimentioning
confidence: 99%